Stable strontium isotope fractionation in marine and terrestrial environments - Stevenson, E (2012)
The work reported in this thesis applies a new isotope tracer, stable strontium isotopes (δ88/86Sr), to address questions concerning changes in global climate that occur in response to continental weathering processes, and to constrain the modern marine geochemical Sr cycle. Stable Sr isotopes are a relatively new geochemical proxy, and as such their behavior needs to be understood in differing forms of marine calcium carbonate, the archives from which records of past stable Sr variability in the oceans can be constructed. Foraminifera, coccoliths and corals (both aragonite and high Mg calcite) acquire δ88/86Sr values lighter than that of modern day seawater, (approximately 0.11, 0.05, 0.2 and 0.19 ‰ lighter than seawater at ~25°C respectively) providing a measureable offset which can be used to constrain the modern Sr outputs from the ocean and provide a better understanding of the modern Sr cycle. Using foraminifera as a sedimentary archive the first marine δ88/86Sr record of seawater over the last two glacial cycles has been constructed, and used to investigate changing carbonate input and output over this 145 kyr period. Modelling of the large excursion of δ88/86Sr to heavier values during Marine Isotope Stage (MIS) 3, reveals that this is more likely to be due to local changes in seawater or post-depositional alteration, rather then whole ocean changes. In the terrestrial environment δδ88/86Sr has been measured in the dissolved load of rivers from the Himalaya. It is found that, in general, rivers draining carbonate catchments possess lighter isotopic δ88/86Sr values than those from rivers draining silicates. Covariations of either δ88/86Sr vs. δ30Si or δ88/86Sr vs. 1/[Sr] can be used to distinguish between rivers draining different catchment areas.